Penerapan Terapi Mindfulness dalam Upaya Meningkatkan Otonomi Warga Binaan di Lembaga Pemasyarakatan Perempuan Kelas IIA Kota Tangerang - Evilia Mulyani; Putri Dian Dia Conia; Puspa Pertiwi (FKIP, Universitas Palangka Raya, 2026)
Female inmates are vulnerable to various psychological challenges that may affect their psychological well-being, particularly their autonomy. This study aimed to examine the effectiveness of mindfulness therapy in improving the autonomy of female inmates at the Class IIA Women’s Correctional Institution in Tangerang. A pre-experimental method with a one-group pretest–double posttest design was employed. The participants consisted of nine female inmates selected based on low to moderate levels of mindfulness and psychological well-being. Data were collected using the autonomy dimension of the Psychological well-being Scale and the Five Facet Mindfulness Questionnaire (FFMQ). The results showed a significant increase in autonomy scores from pretest to posttest t(8) = -5.933, p < .001). The average N-Gain score was 0.50, indicating a moderate level of effectiveness. These findings suggest that mindfulness therapy was effective in enhancing the autonomy of female inmates. The results were further supported by participants’ worksheets, which indicated improvements in their ability to consider the consequences of their actions, regulate their emotions, and make decisions more independently.